Improving marinade absorption and shelf life of vacuum packed marinated pork chops through the application of high pressure processing as a hurdle. (September 2019) - O'Neill, Ciara M.; Cruz-Romero, Malco C.; Duffy, Geraldine; Kerry, Joseph P.
Highlights: High pressure processing (HPP) was used to accelerate marinade absorption in pork The marinade masked the discolouration/whitening effect of HPP on raw pork Texture was negatively affected after HPP; however tenderness increased over storage The shelf life increase of the pork chops depended on the pressure level applied Abstract: The objective of this study was to determine the efficacy of HPP to accelerate marinade (piri-piri) absorption in pork chops and to study the effects on the physicochemical, sensory and microbiological characteristics during storage. HPP (300 MPa, 400 MPa or 500 MPa) and organic acids Inbac ™ (0.3%) were used as hurdles to extend the shelf life. The results showed that HPP ≥ 400 MPa increased ( P < 0.05) the marinade absorption which enhanced the flavour acceptability of the marinated pork chops. The piri-piri marinade masked the discolouration caused by HPP and increased ( P < 0.05) the tenderness of the pork chops over storage. From the microbiological point of view, HPP at 300, 400 or 500 MPa and Inbac™ (0.3%) extended ( P < 0.05) the shelf life by 16, 22 and 29 days, respectively. The results highlighted the potential of combined effects of HPP and antimicrobial Inbac™ to accelerate marinade absorption and extend the shelf life of marinated pork chops.